Governance Indicators for Strategic Business Decisions: Diversity of Western Asian Countries in Terms of Democracy - Alhanaqtah, Omar Jraid Mustafa; Alhanaqtah, Veronika Vladimir Alexey (Asian Economic and Financial Review, 2018)
The main objective of the research is to configure the countries of Western Asia from the standpoint of governance with a particular focus on democracy indicator. We are interested in the government indicators because since the times of Washington consensus the foreign aid paradigm has changed: a priority is given to funding development programs in countries with good governance. In order to measure the progress there is the need to quantify differences in governments among nations and to measure its quality. Governance indicators and the Democracy Index as well, are also supposed to help business leaders in strategic decisions. Comparative analysis technique and a concept of correlation are used as a methodology of the research while configuring the countries of Western Asia in terms of democracy. It is verified whether the more democratic countries in the region are the more trustful and prosperous societies. It is debated whether there is the need for democracy so as to reach good governance and economic growth.